Numerical study of the effects of crack location on creep crack growth in weldment - Saber, Mohammed; Sun, Wei; Hyde, T.H. (Elsevier, 2016)
A numerical study on the effects of crack location on creep crack growth, in a P91 weldment, was carried out using a finite element package (ABAQUS). Models of compact tension specimens were used. The obtained results showed that, the creep crack growth in the weld metal are much higher than that in the parent metal. However, the creep crack growth in cross-weld specimens is controlled by the properties of the weakest component of the weld. This highlights the importance of the heat affected zone (HAZ) as the weakest region of the weldment. Effects of the width of HAZ are presented, too.